Respuesta :
6w4+8w2
step-by-step.w2(−4w2−2)+(−5w2)(−2w2−2)Distribute:=(w2)(−4w2)+(w2)(−2)+(−5w2)(−2w2)+(−5w2)(−2)=−4w4+−2w2+10w4+10w2Combine Like Terms:=−4w4+−2w2+10w4+10w2=(−4w4+10w4)+(−2w2+10w2)=6w4+8w2 answer
step-by-step.w2(−4w2−2)+(−5w2)(−2w2−2)Distribute:=(w2)(−4w2)+(w2)(−2)+(−5w2)(−2w2)+(−5w2)(−2)=−4w4+−2w2+10w4+10w2Combine Like Terms:=−4w4+−2w2+10w4+10w2=(−4w4+10w4)+(−2w2+10w2)=6w4+8w2 answer
Answer:
6w⁴ + 8w²
Explanation:
Before we begin, remember the following:
xᵃ * xᵇ = x⁺ᵇ
+ve * -ve = -ve
-ve * -ve = +ve
+ve * +ve = +ve
To solve this problem, we will follow the following steps:
1- get rid of the brackets using the distributive property
2- combine like terms
This can be shown as follows:
w²(-4w² - 2) + (-5w²)(-2w² - 2)
w²(-4w²) + w²(-2) + (-5w²)(-2w²) + (-5w²)(-2)
-4w⁴ - 2w² + 10w⁴ + 10w²
w⁴(-4+10) + w²(-2+10)
6w⁴ + 8w²
Hope this helps :)
6w⁴ + 8w²
Explanation:
Before we begin, remember the following:
xᵃ * xᵇ = x⁺ᵇ
+ve * -ve = -ve
-ve * -ve = +ve
+ve * +ve = +ve
To solve this problem, we will follow the following steps:
1- get rid of the brackets using the distributive property
2- combine like terms
This can be shown as follows:
w²(-4w² - 2) + (-5w²)(-2w² - 2)
w²(-4w²) + w²(-2) + (-5w²)(-2w²) + (-5w²)(-2)
-4w⁴ - 2w² + 10w⁴ + 10w²
w⁴(-4+10) + w²(-2+10)
6w⁴ + 8w²
Hope this helps :)